Red Gold in Peril: A Multidimensional Analysis of Threat to Cultivation of Saffron in India: OPINION PAPER - Bhagat, Nancy; Ali, Tahir; Vakhlu, Jyoti (Annals of Arid Zone, 2025)
This paper highlights the threats to saffron cultivation in India. Based on a review of the literature combined with our experience in saffron research, climate change seems to be the primary threat followed by corm rot disease and rapid urbanization. Additional challenges include spice adulteration, limited availability of good quality corms, unsustainable aeroponic/hydroponic practices that deplete corms from traditional sites and manual cultivation practices. To ensure the sustainability of this heritage crop, this study emphasizes the need for geographic diversification, strategies to prevent injury to corms, post-harvest processing, protective policies and technological modernization for saffron cultivation.